Tanjung Jaya Village and the Potential for Developing Ethno-Sciences for Climate Change Mitigation in Panimbang District, Banten - Sulistya, Astrid; Ibrahim, Riza (International Journal of Ethno-Sciences and Education Research, 2025)
Climate change is a major challenge for global society, especially in coastal areas that are vulnerable to the impacts of environmental change. Tanjung Jaya Village in Panimbang District, Banten, is an example of a coastal area that faces major threats due to climate change, such as coastal abrasion, tidal flooding, and changes in weather patterns. The people of Tanjung Jaya Village have rich local knowledge, which has been passed down from generation to generation and has proven effective in managing natural resources and mitigating disasters. This study aims to explore the potential of ethno-sciences or ethnology in addressing the impacts of climate change in this village, with a focus on mangrove management, sustainable agriculture, and coastal ecosystem protection. The results of the study indicate that the integration of traditional knowledge with modern science, such as satellite-based monitoring technology, can increase the effectiveness of climate change mitigation. Therefore, the development of policies that support the strengthening of the role of local wisdom in mitigating climate change is very much needed to increase community resilience to natural disasters